2014
DOI: 10.1038/bmt.2014.228
|View full text |Cite
|
Sign up to set email alerts
|

Severe weight loss in 3 months after allogeneic hematopoietic SCT was associated with an increased risk of subsequent non-relapse mortality

Abstract: Patients after allogeneic hematopoietic SCT (HSCT) are at risk of malnutrition. To assess the impact of malnutrition after allogeneic HSCT on transplant outcomes, we conducted a retrospective study. Adult patients who received allogeneic HSCT from 2000 to 2009 for standard-risk leukemia and achieved disease-free survival up to 3 months after allogeneic HSCT were included. From participating centers, 145 patients were enrolled. Median age was 46 years (19-68). Patients were classified based on weight loss durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 36 publications
(38 reference statements)
2
66
1
3
Order By: Relevance
“…Our group reported that severe weight loss ( 10% weight loss in 3 months) after allogeneic HSCT was associated with an increased risk of subsequent NRM, which led to a poor overall survival [38]. Bassim et al also reported that patients with malnutrition had inferior outcomes compared with those without malnutrition.…”
Section: Nutritional Management In Long-term Follow-up Unitmentioning
confidence: 90%
See 1 more Smart Citation
“…Our group reported that severe weight loss ( 10% weight loss in 3 months) after allogeneic HSCT was associated with an increased risk of subsequent NRM, which led to a poor overall survival [38]. Bassim et al also reported that patients with malnutrition had inferior outcomes compared with those without malnutrition.…”
Section: Nutritional Management In Long-term Follow-up Unitmentioning
confidence: 90%
“…Regarding undernutrition, weight loss is rather common after allogeneic HSCT [38,[87][88][89][90][91][92][93]. Our group reported that severe weight loss ( 10% weight loss in 3 months) after allogeneic HSCT was associated with an increased risk of subsequent NRM, which led to a poor overall survival [38].…”
Section: Nutritional Management In Long-term Follow-up Unitmentioning
confidence: 97%
“…Our data are in line with previous studies looking at associations of nutritional parameters and outcomes in patients with haematological malignancies. One recent retrospective study from Japan including 145 adult patients who received allogeneic HSCT from 2000 to 2009 reported a step-wise increase in the cumulative incidences of 2-year non-relapse mortality from 3.8% in the normal group up to 27.3% in the severe malnutrition group defined based on the post-HSCT weight loss of >10% [28] . The same researchers also found that underweight patients before HSCT was a risk factor for mortality with a roughly 10% increase in risk [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Negative Auswirkungen eines raschen Gewichtsverlusts auf die Mortalität sind etwa für Patienten nach allogener Stammzelltransplantation belegt [20]. …”
Section: Referentin: Monika Reuss-borst Bad Kissingen Für Den Arbeiunclassified